Queen of the Hanukkah dosas - Ehrenberg, Pamela (Farrar Straus Giroux, 2017)
A boy is worried that his little sister's climbing will spoil the first night of Hanukkah, when his family combines his father's Jewish traditions with his mother's East Indian cooking.